Antibodies against the erythroferrone N-terminal domain prevent hepcidin suppression and ameliorate murine thalassemia - Arezes, J; Foy, N; McHugh, K; Quinkert, D; Benard, S; Sawant, A; Frost, J; Armitage, A; Pasricha, S; Lim, P; Tam, M; Lavallie, E; et al. (American Society of Hematology, 2020)
Erythroferrone (ERFE) is produced by erythroblasts in response to erythropoietin (EPO) and acts in the liver to prevent hepcidin stimulation by BMP6. Hepcidin suppression allows for the mobilization of iron to the bone marrow for the production of red blood cells. Aberrantly high circulating ERFE in conditions of stress erythropoiesis, such as in patients with β-thalassemia, promotes the tissue iron accumulation that substantially contributes to morbidity in these patients. Here we developed antibodies against ERFE to prevent hepcidin suppression and correct the iron loading phenotype in a mouse model of β-thalassemia (Hbb(th3/+) mice) and used these antibodies as tools to further characterize ERFE’s mechanism of action. We demonstrate that ERFE binds to BMP6 with nanomolar affinity, and binds BMP2 and BMP4 with somewhat weaker affinities. We show that BMP6 binds the N-terminal domain of ERFE, and a polypeptide derived from the N-terminus of ERFE was sufficient to cause hepcidin suppression in Huh7 hepatoma cells and in wildtype mice. Anti-ERFE antibodies targeting the N-terminal domain prevented hepcidin suppression in ERFE-treated Huh7 cells and in EPO-treated mice. Finally, we observed a decrease in splenomegaly and in serum and liver iron in anti-ERFE treated Hbb(th3/+) mice, accompanied by an increase in red blood cells and hemoglobin and decrease in reticulocyte counts. In summary, we demonstrate that ERFE binds BMP6 directly and with high affinity, and that antibodies targeting the Nterminal domain of ERFE that prevent ERFE-BMP6 interactions constitute a potential therapeutic tool for iron-loading anemias.